A Search for New Variable and Proper Motion Stars in the Galactic Disk - Benjamin, Robert A (Proceedings of the Wisconsin Space Conference, 2016)
Mid-infrared observations of sections of the Galactic Plane with the NASA Spitzer Space Telescope at two widely spaced epochs (2004-5) and (2012-13) have opened up the possibility of a large-scale search for variable stars, proper motion stars, and transients. This has required developing a new research infrastructure to merge and compare the two epochs of observations, and has led to the discovery of a surprising number of variable sources (over 100,000) and high proper motion sources (over 400). We quantify the probability that a star observed in the mid-infrared will show variability at a certain amplitude. For stars with apparent infrared magnitude fainter than m=10, stars have a 0.6% probability of varying by more than 0.25 magnitudes, but this probability increases to 14% for stars with m=6. We also describe upcoming observations of the center of the Milky Way Galaxy.